Dissecting the regulatory landscape of the Abd-B gene of the bithorax complex. - Mihaly, J.; Barges, S.; Sipos, L.; Maeda, R.; Cleard, F.; Hogga, I.; Bender, W.; Gyurkovics, H.; Karch, F. (Development, 2006)
The three homeotic genes of the bithorax complex (BX-C), Ubx, abd-A and Abd-B control the identity of the posterior thorax and all abdominal segments. Large segment-specific cis-regulatory regions control the expression of Ubx, abd-A or Abd-B in each of the segments. These segment-specific cis-regulatory regions span the whole 300 kb of the BX-C and are arranged on the chromosome in the same order as the segments they specify. Experiments with lacZ reporter constructs revealed the existence of several types of regulatory elements in each of the cis-regulatory regions. These include initiation elements, maintenance elements, cell type- or tissue-specific enhancers, chromatin insulators and the promoter targeting sequence. In this paper, we extend the analysis of regulatory elements within the BX-C by describing a series of internal deficiencies that affect the Abd-B regulatory region. Many of the elements uncovered by these deficiencies are further verified in transgenic reporter assays. Our results highlight four key features of the iab-5, iab-6 and iab-7 cis-regulatory region of Abd-B. First, the whole Abd-B region is modular by nature and can be divided into discrete functional domains. Second, each domain seems to control specifically the level of Abd-B expression in only one parasegment. Third, each domain is itself modular and made up of a similar set of definable regulatory elements. And finally, the activity of each domain is absolutely dependent on the presence of an initiator element.